Volatiles of Geranium purpureumVill. and Geranium phaeum L.: Chemotaxonomy of Balkan Geranium and Erodium Species (Geraniaceae). Issue 11 (November 2013) - Radulović, Niko S.; Dekić, Milan S.
Abstract The essential oils obtained by hydrodistillation of Geranium purpureum and G. phaeum were characterized by GC‐FID and GC/MS analyses (the former for the first time in general). In total, 154 constituents were identified, accounting for 89.0–95.8% of the detected GC peak areas. The investigated essential oils consisted mainly of fatty acids and fatty‐acid‐derived compounds (45.4–81.3%), with hexadecanoic acid and (E)‐phytol as the major components. The chemotaxonomic significance of the variations in the essential‐oil composition/production of the presently and previously investigated Geranium and highly related Erodium taxa from Serbia and Macedonia was assessed by multivariate statistical analyses. The main conclusions drawn from the high chemical similarity of the two genera, visible from the obtained dendrograms and biplots, confirm the close phylogenetic relationship between the investigated Geranium and Erodium taxa, i.e., that there is no great intergeneric oil‐composition variability. Changes in the composition and production of essential oils of the herein investigated taxa and 60 other randomly chosen species belonging to different plant genera were also statistically analyzed. The results put forward pro arguments for the oil‐yield–oil‐composition correlation hypothesis.